Linguistic tone and the small trader: Measurement issues, regulatory implications, and directions for future research - Loughran, Tim (Accounting, Organizations and Society, 2018)
Baginski, Demers, Kausar, and Yu (2018) demonstrate that small, retail investors often misinterpret the linguistic tone contained in managerial forecast announcements during the 1997-2006 time period. This is in contrast to the trading behavior of large, institutional investors. My commentary offers some concerns/suggestions about the measurement of linguistic tone, the separation of small and large traders’ activities, the implications of this type of research for regulatory actions, and includes possible additional research suggested by their paper.